2005
DOI: 10.1111/j.1835-2561.2005.tb00288.x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Intangible Capital: A Review of Current Practice

Abstract: This paper examines international practices that measure firm‐level investments into intangible capital. The issues motivating the paper are the need for a standardised framework for measuring intangible capital and the possibility for standardised applications of these measures into the future. The paper analyses the differences and problems associated with the properties of the “official” (accounting) and “non‐official” measurement approaches. We propose that the way to a standardised, more comparable approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 53 publications
3
57
0
3
Order By: Relevance
“…Hunter, Webster and Wyatt (2005) explain that a prime motivation for external disclosure of IC is signalling expected future growth of the firm to external stakeholders.…”
Section: Signallingmentioning
confidence: 99%
“…Hunter, Webster and Wyatt (2005) explain that a prime motivation for external disclosure of IC is signalling expected future growth of the firm to external stakeholders.…”
Section: Signallingmentioning
confidence: 99%
“…A number of competing and diverse frameworks for the measurement, management and disclosure of intellectual capital exist in the current literature (Hunter, Webster & Wyatt, 2005;Kaufmann & Schneider, 2004). One of the most widely accepted is the Intellectual Capital Approach which is supported by a number of prominent authors in the field (see for example Brooking, 1996;Edvinsson & Malone;Kaplan & Norton, 1992;Roos, Roos, Dragonetti & Edvinsson, 1997;Rodgers, 2003;Stewart, 1997;Sveiby, 1997).…”
Section: Reviewmentioning
confidence: 99%
“…There are other classifications as well, but the differences are often rather related to the form than to the contents. Usually, intangible capital is considered equivalent to intellectual capital, but specialized literature (Hunter et al, 2005) showed that between them there is an inclusion relation, not equality. Intellectual capital could be assimilated to human capital, meaning the totality of the employees' knowledge and skills.…”
Section: Introduction Intangible Assets: New Sources For Developmentmentioning
confidence: 99%